Structural Characterization of NiO/Cr2O3Composites and Hydrothermal Synthesis, Properties Gas Sensing - Mohammed, Ghuson H; Hassan, Tunis B; Abdulhamied, Zainab T (Al-Nahrain Journal of Science, 2018)
Pure Cr2O3 and NiO/Cr2O3 nanocomposite were luckily synthesized by simple hydrothermal technique. X-ray films diffraction (XRD), Filed Emission scanning electron microscopy (FESEM), Energy dispersive X-ray spectroscopy (EDS), were used to research the crystalline structures, surface morphologies and nanostructures, and element components and their valences of the as-synthesized samples. Moreover, gas sensors based on the synthesized pure Cr2O3 and NiO/ Cr2O3 composites were fabricated and their sensing behavior, to NH3.Gas sensing experiments reference that the NiO/ Cr2O3 composites showed much higher gas response and lower working temperature than those of pure Cr2O3. These results assure that the as-synthesized NiO/ Cr2O3 composites a favorable NH3 sensing material